Smart Manufacturing in Engineering Management: A Review of Industry 4.0 Implementation Strategies - Eslami, Sina (Management Strategies and Engineering Sciences, 2021)
The rise of Industry 4.0 marks a pivotal shift in manufacturing, driven by the convergence of advanced digital technologies such as the Internet of Things (IoT), artificial intelligence (AI), and big data analytics. This narrative review examines the strategies employed by organizations to implement Industry 4.0 within the context of smart manufacturing and engineering management. The review identifies key challenges and barriers to adoption, including significant financial investments, technical complexities, and organizational resistance to change. Despite these challenges, Industry 4.0 offers substantial opportunities for innovation, operational efficiency, and the development of new business models, particularly in industries like automotive and electronics. The review also highlights varying levels of success across different industries, with a focus on the critical role of engineering management in navigating the transformation. Future research directions are proposed, emphasizing the need for empirical studies on the impact of Industry 4.0 technologies on organizational performance and the social and ethical implications of these technologies. The findings of this review have significant implications for both practitioners and policymakers, providing a roadmap for successful Industry 4.0 implementation.